Effective dietary interventions during pregnancy: a systematic review and meta-analysis of behavior change techniques to promote healthy eating - Hannah O’Connor; Nina Meloncelli; Shelley A. Wilkinson; Anna Mae Scott; Lisa Vincze; Alita Rushton; Samantha Dawson; Jenna Hollis; Bree Whiteoak; Sarah Gauci; Susan de Jersey (BMC Pregnancy and Childbirth)
Abstract Improving dietary intake during pregnancy can mitigate adverse consequences for women and their children. The effective techniques and features for supporting and sustaining dietary change during pregnancy and postpartum are minimally reported. The primary aims of this systematic review and meta-analysis were to summarise the effectiveness of dietary interventions for pregnant woman, identify which behaviour change techniques (BCTs) and intervention features were most frequently used and determine which were most effective at improving dietary intake. Six databases were searched to identify randomised control trials (RCTs) reporting on dietary intake in pregnant women over the age of sixteen, with an active intervention group compared to a control group receiving usual care or less intensive interventions. The Cochrane Risk of Bias Tool 1 was used to assess study validity. BCTs were coded by two authors using Michie et al.’s BCT taxonomy V1. A random effect model assessed intervention effects on indices of dietary quality and food groups (fruit, vegetables, grains and cereals, meat, and dairy) in relation to the use of BCTs and intervention features. Thirty- seven RCTs met the inclusion criteria. High heterogeneity was observed across intervention characteristics and measures of fidelity. Only half of the available BCTs were used, with eleven used once. The BCT category Reward and threat was successful in improving dietary quality and vegetable intake, whilst 'Action planning’ (1.4) from the category Goals and planning significantly improved dietary quality. Interventions delivered by a nutrition professional and those that included group sessions improved dietary quality more than those delivered by other health professionals, research staff, or application-delivered interventions and delivered via other modalities. Future dietary interventions during pregnancy should incorporate and report on BCTs used in the intervention. Successful design elements for improving antenatal dietary intake may include multimodal interventions delivered by nutrition professionals and the use of Rewards and Goal setting.